The Influence of Organizational Culture and Work Environment on the Performance of Naval Command and Staff Collage (Seskoal) With Job Satisfaction - Zukarnaen Zukarnaen; Dedi Purwana; Ari Saptono (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2020)
Staff performance is very crucial in the sustainability of the company. Some factors that are thought to strongly influence performance are organizational culture, work environment, and job satisfaction. Thus, the study aimed to analyze the strong influence of organizational culture and work environment on job satisfaction, then to analyze the strong influence of organizational culture and work environment on performance, then analyze the effect of job satisfaction on performance, finally to find out and analyze the indirect effect of organizational culture and work environment towards the performance of Seskoal soldiers through job satisfaction. This research uses quantitative methods with data obtained through questionnaires with Likert scale assessment. With a total of 137 Seskoal soldiers. The analysis results show that organizational culture and work environment with job satisfaction are positively and significantly related, organizational culture and work environment with performance are positively and significantly related, job satisfaction with performance is positively and significantly related, there is a relationship between the influence of organizational culture and performance with mediated by job satisfaction and there is a relationship between the influence of the work environment with performance mediated by job satisfaction. Keywords: Organizational Culture, Work Environment, Job Satisfaction